Bandwidth choice for robust nonparametric scale function estimation - Boente Boente, Graciela Lina (2012)
We introduce and compare several robust procedures for bandwidth selection when estimating the variance function. These bandwidth selectors are to be used in combination with the robust scale estimates introduced by Boente et al. (2010a). We consider two different robust cross--validation strategies combined with two ways for measuring the cross--validation prediction error. The different proposals are compared with non robust alternatives using Monte Carlo simulation. We also derive some asymptotic results to investigate the large sample performance of the corresponding robust data--driven scale estimators.